Role of Loss Aversion, Representativeness, and Overconfidence in Investment Decision-Making - Shrestha, Sajeeb Kumar; Karki, Pravesh; Shrestha, Nayan; Karki, Tej Bahadur; Mahat, Dipak; Neupane, Dasarath (International Journal of Humanities, Education, and Social Sciences, 2025)
This study investigates how behavioral biases loss aversion, representativeness, and overconfidence influence investment decisions in Nepal’s stock market. Using a descriptive and causal research design, data were collected via structured questionnaires from 120 individual investors. Analysis through SPSS revealed that overconfidence has a significant positive impact on investment decisions, while loss aversion and representativeness showed moderate but insignificant effects. These findings highlight the critical role of psychological factors in shaping investor behavior, offering insights for financial advisors and policymakers to mitigate bias-driven risks.